Hubungan Budaya Optimis Akademik Guru Besar dengan Kualiti Guru Sekolah Rendah di Daerah Kuala Langat - Yusoff, Siti Afifah; Mohd Nor, Mohamed Yusoff (Selangor Humaniora Review, 2019)
Academic optimism culture is a dynamic element in the 21st century school culture in line with current educational developments. In this regard, the purpose of this study is to identify the relationship between the academic optimism of the headmaster and the quality of primary school teachers in the district of Kuala Langat. This study is a quantitative survey. Data was obtained by distributing questionnaire to 50 respondents from various areas of expertise randomly selected from 12 primary schools in the district of Kuala Langat. The data obtained were analyzed using descriptive method to explain the mean score and the standard deviation in describing each dimension studied using Statistical Packages for Social Science (SPSS) version 22. The findings show that the headmasters practise academic optimism in their respective schools at moderate levels. Therefore, it can be concluded that there is a relationship between academic optimism culture of the headmasters and the quality of primary school teachers in the district of Kuala Langat. This shows that each teacher's roles and responsibilities are very important and have a profound effect on their professional practices.